Assessment of soil and water quality status of rose growing areas of Rajasthan and Uttar Pradesh, India - LR, Varalakshmi; P, Tejaswini; S, Rajendran; K K, Upreti (Journal of Horticultural Sciences, 2021)
Rose is a commercial flower crop widely grown across India. It is highly sensitive to salinity and alkalinity. In the process of identification of salt and alkalinity resistant rootstocks of rose cultivars, a survey was conducted in the rose growing areas of Uttar Pradesh (UP) and Rajasthan. Total of 28 representative surface soil samples were collected from rose fields of these regions, processed and analyzed for the soil quality parameters. Similarly water samples (20 samples) from the bore wells of these fields were collected and analyzed. The results revealed that most of the soils of rose growing fields in UP were alkaline (pH >8.0) with normal salt content (electrical conductivity, EC < 0.5 dS m-1). Many of these soils also had higher bicarbonates (> 3 meq 100 g-1). In case of Rajasthan, few samples had higher pH, EC, chloride (>2 meq 100 g-1) and bicarbonate contents. Exchangeable sodium percentage (ESP) of UP and Rajasthan samples ranged from 5.21-20.7% and 2.94-24.9%, respectively. In case of water parameters in these areas, pH was slightly in alkaline range, EC of some of the samples were high (>1 dSm-1). Sodium content was slightly higher than other cations. Soluble sodium percentage (SSP) of water samples was also slightly higher than normal range (0-50%). Few samples had slightly higher chloride above the threshold limit. From the results, it is concluded that soil and water quality of the rose growing areas of UP and Rajasthan is marginal and proper management/reclamation measures need to be carried out for sustaining the production system.
Keywords: Rajasthan; rose; Soil quality; Uttar Pradesh; water quality